2022
DOI: 10.29121/granthaalayah.v10.i7.2022.4690
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ethical Climate, Organizational Culture, on Organizational Performance in Tax Service Offices Mediated by Strategic Service Management

Abstract: The purpose of this study is to change the duties and functions of the Tax Service Office as part of the strategic plan of the Director General of Taxes 2020-2024 to increase the effectiveness of tax compliance supervision. Changes in the duties and functions of the Tax Service Office are aimed at expanding the tax base which is the main mission of the Director General of Taxes in order to increase tax revenues. in an effort to increase voluntary compliance, regarding the 3C (Click, Call and Counter). that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Moreover, the relationship between ethical climate, organizational culture, and organizational performance has been investigated, highlighting the mediating role of strategic service management in tax service offices (Zatna et al, 2022). Additionally, research has shown that organizational culture significantly affects employee retention, job satisfaction, and organizational commitment, while climate impacts human resource management, strategy, and performance (Robinson & Reddy, 2016).…”
Section: Organizational Culture Structure and Climatementioning
confidence: 99%
“…Moreover, the relationship between ethical climate, organizational culture, and organizational performance has been investigated, highlighting the mediating role of strategic service management in tax service offices (Zatna et al, 2022). Additionally, research has shown that organizational culture significantly affects employee retention, job satisfaction, and organizational commitment, while climate impacts human resource management, strategy, and performance (Robinson & Reddy, 2016).…”
Section: Organizational Culture Structure and Climatementioning
confidence: 99%
“…2020) that improving organizational culture has an impact on improving the service quality of university staff in Indonesia. In this regard, ethical climate and organizational culture have positive and significant results on strategic service management (Zatna et al, 2022). Alshemmari (2020) even found the results that there was a significant effect of the prevailing organizational culture on the quality of services provided by the Ministry of Industry and Trade in Kuwait.…”
Section: The Importance Of Service Climate and Culture Climate In The...mentioning
confidence: 99%